Strategi Pengembangan Sistem Pemerintahan Berbasis Elektronik (SPBE) dalam Menunjang Pelayanan Publik Kantor Desa Ngembul Kecamatan Binangun Kabupaten Blitar - Ferida Asih Wiludjeng (PT PUSTAKA CENDEKIA GROUP, 2025)
The purpose of this study is to explain the development of an electronic-based government system (SPBE) used for public service delivery activities. The public service information system at the Ngembul Village Office, Binangun District, Blitar Regency still uses a manual system, thus becoming an obstacle to the implementation of services to the community. The method used in this study is a qualitative approach. The technique used for analysis is a SWOT analysis to determine the strengths, weaknesses, opportunities, and threats in developing an electronic-based service system to provide services to the community. Based on the results of the SWOT analysis, 4 (four) strategies were obtained that can be used to develop an electronic-based government system (SPBE) in public service delivery activities at the Ngembul Village Office. The SO strategy is formulated with the existence of a system to regulate services that requires good system planning and is supported by sophisticated information technology facilities. The ST strategy is shown by the existence of a system that regulates electronic-based administrative services, can reduce the level of document falsification and the licensing application process with the support of information technology can be easier and faster. The WT and WO strategies are essentially the same: advances in technology and the internet can facilitate faster and more accessible dissemination of information about services at the Ngembul Village Office. Furthermore, good coordination between management and employees can improve the quality of service to the public.